Epibatidine Induces Long-Term Potentiation (LTP) via Activation of α4β2 Nicotinic Acetylcholine Receptors (nAChRs) In Vivo in the Intact Mouse Dentate Gyrus: Both α7 and α4β2 nAChRs Essential to Nicotinic LTP - Shogo Matsuyama; Akira Matsumoto (Elsevier, 2003)
ABSTRACT: Activation of nicotinic acetylcholine receptors (nAChRs) induces nocotinic long-term potentiation (LTPn) in vivo in the mouse dentate gyrus. We have found that α4β2 nAChRs activated by epibatidine induce LTPn, the full size of which requires the involvement of α4β2 and α7 nAChRs, in the intact mouse dentate gyrus using extracellular recording techniques. Intraperitoneal application of epibatidine, a potent α4β2 nAChR agonist, at 0.3 - 3.0 μg/kg induced a long-lasting increase similar to LTPn induced by choline, a selective α7 nAChR agonist, and at 10 μg/kg caused a transient increase followed by a depression. The LTPn induced by epibatidine at 3.0 μg/kg or choline at 30 mg/kg was significantly suppressed by pre-treatment but not post-treatment with mecamylamine (0.5 mg/kg, i.p.), a non-selective neuronal nicotinic antagonist. Post-application of nicotine at 3.0 mg/kg enhanced epibatidine-induced LTPn to the same level of nicotine-induced LTPn, but post-application of epibatidine had no effect on nicotine-induced LTPn. Epibatidine-induced LTPn was additionally increased by post-application of choline, and vice versa, reaching the same level of nicotine-induced LTPn. The present study revealed that epibatidine induced the LTPn via α4β2 nAChRs and that both α7 and α4β2 nAChRs were essential for full-sized LTPn, suggesting that both nAChRs play an important role in synaptic plasticity.